Analisis Perilaku Khalayak dalam Mengonsumsi Konten Edukasi Karier di TikTok sebagai Media Pembelajaran Nonformal - Vebriyanti Vebriyanti; Rendra Widyatama (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study examines audience behavior in consuming career education content on TikTok as a form of nonformal learning. The rapid growth of social media has transformed how individuals access information, including career-related knowledge. This research aims to analyze user motivations, consumption patterns, and responses toward career education content. A qualitative descriptive approach was employed, involving 54 respondents aged 20–30 years who have accessed career-related content on TikTok. Data were collected through open-ended questionnaires and content analysis of the TikTok account @Vinamuliana. The findings reveal that information needs are the primary motivation for content consumption, followed by self-improvement and inspiration. In terms of consumption patterns, most users access content through the For You Page (FYP), indicating the significant role of platform algorithms, although some users actively search for content. User responses vary, ranging from real actions such as improving CVs and applying tips, to understanding without action, and no response at all. These results suggest that TikTok functions not only as an entertainment platform but also as an effective nonformal learning medium that provides practical and relevant career information. The study implies that short-form, visual, and practical content can enhance user engagement and support learning outcomes in digital environments.